Antisense inhibition of enolase strongly limits the metabolism of aromatic amino acids, but has only minor effects on respiration in leaves of transgenic tobacco plants - Voll, Lars M.; Hajirezaei, Mohammad R.; Czogalla-Peter, Caecilia; Lein, Wolfgang; Stitt, Mark; Sonnewald, Uwe; Boernke, Frederik (New Phytologist, 2009)
We conclude that a decrease in enolase activity affects secondary pathways, such as the shikimate branch of amino acid biosynthesis, but does not inhibit the rate of respiration.
Keywords: amino acids; antisense; enolase; glycolysis; phosphoenolpyruvate